Super-efficiency Performance of Malaysian Banking Industry - Farhana, Ismail; Rossazana, Ab-Rahim; Nur-Zaimah, Ubaidillah (Universiti Malaysia Sarawak (UNIMAS), 2013)
While past banking efficiency studies had tended to focus on quantifying the efficiency of financial institutions, few attempts were undertaken to compare the efficiency performance of domestic and foreign banks; and even fewer to compare the super-efficiency performance of both banks. By addressing the above discussion as the gap in the literature, this study contributes to the existing literature by utilising Data Envelopment Analysis to super-efficiency scores for individual banks. The first objective of this study is to estimate technical efficiency and its decompositions, which are pure technical and scale efficiency as well as to estimate super-efficiency index of Malaysian banks for the study period 2000 to 2010. The results indicate that in general, domestic banks perform better than foreign banks. However, the super-efficiency results reveal that on efficiency performance per individual banks; individual foreign banks are more efficient than individual domestic banks. The findings are valid across technical efficiency and its decompositions, which are pure technical efficiency and scale efficiency